Institutional Ownership as a Moderator in the Relationship Between Enterprise Risk Management, Profitability, and Firm Value - Sari, Ni Putu Hanna Windu; Kresnandra, Anak Agung Ngurah Agung; Sujana, I Ketut (E-Jurnal Akuntansi, 2025)
Firm value is an indicator of a company's condition, reflected through its share price. This research aims to provide empirical evidence on the influence of Enterprise Risk Management (ERM) and profitability on firm value, as well as the moderating effect of institutional ownership on the relationships between ERM, profitability, and firm value. The population for this study consists of companies within the banking subsector listed on the Indonesia Stock Exchange (IDX) over the period 2020-2022. A nonprobability sampling method was utilized, yielding a sample of 63 observations. Data were analyzed using Moderated Regression Analysis. The results indicate that ERM and profitability positively impact firm value. Additionally, institutional ownership strengthens the effects of ERM and profitability on firm value. Keywords: Firm value; Enterprise Risk Management; Profitability; and Institutional Ownership